HER2/neu immunohistochemical expression in gastric carcinoma - Sadanandan, Anjali; C. N., Arunraj (International Journal of Research in Medical Sciences, 2020)
Background: Gastric carcinoma is a deadly disease with high mortality. A better understanding of the molecular basis of gastric cancer has contributed to the development of rationally designed molecular targeted therapies which will improve the survival rate. A genetic alteration that could help in targeted therapy and prognostication includes Human Epidermal Growth Factor Receptor 2 (HER2/neu) overexpression in gastric carcinoma. The objective of the present study was to identify and evaluate the HER2/neu protein immunohistochemical expression in gastric cancer from biopsies and surgical resection specimens and to evaluate their correlation with histopathological features. Methods: Total/subtotal gastrectomy specimens and gastric biopsies from a tertiary care center in South India were included in the study and assessed by light microscopy and Immunohistochemistry (IHC). Results: HER2/neu overexpression was seen in 28.6% of gastric adenocarcinoma. HER2/neu overexpression was seen in 44.2% of intestinal-type and 20% of mixed type with none of the diffuse type exhibited HER2/neu positivity and this was statistically highly significant with p value of <0.01. HER2/neu positivity was found in 50% well-differentiated and 36.4% moderately differentiated tumors with none of the poorly differentiated tumors exhibiting HER2/neu positivity and this was statistically highly significant with p value of <0.01. Conclusions: This study highlights the importance of the identification of HER2/neu overexpression in gastric adenocarcinoma. This will help in prognostication and identifying patients suitable for novel therapeutic interventions which will help in prolongation of survival of patients with this deadly disease.